Growth and assembly of oxide nanowire. - Phyo, Baw Swe. (2013)
In this thesis, systematic researches on synthesis of nanowires via VLS mechanism and comprehensive analysis on physical properties of ITO nanowires have discussed. SEM and XRD measurement reveals nanowire synthesized by VLS method has very high purity and good crystallinity. Resistivity measurement on a single ITO nanowire has been carried out and it gives remarkable conductivity of 7.263±0.09 μΩ.m with EBL based measurement. Lastly, considering this splendid conductivity, some applications on future electronic devices have discussed.